Smarter metrics in climate change and agriculture Business guidance for target-setting across productivity, resilience and mitigation. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
This collaborative publication is publicaly available (namely promoted accross the 200 WBCSD companies)